Evaluation of enhanced production of cellulose deconstructing enzyme using natural and alkali pretreated sugar cane bagasse under the influence of graphene oxide. (December 2021) - Srivastava, Neha; Mohammad, Akbar; Singh, Rajeev; Srivastava, Manish; Syed, Asad; Bahadur Pal, Dan; Elgorban, Abdallah M.; Mishra, P.K.; Gupta, Vijai Kumar
Graphical abstract: Highlights: Evaluates cellulase production using natural and pretreated sugar cane bagasse. Enhanced cellulase production induced by graphene oxide employed as a catalyst. Maximum 25 IU/gds cellulase is produced using 0.5% alkali & 1.5% GO in 72 h at pH 5.0. Graphene oxide catalyzes ∼ 100 % higher enzymatic activity using untreated SCB. Graphene oxide catalyzes ∼ 58.33 % higher enzymatic activity using pretreated SCB. Abstract: High production cost of cellulase enzyme is one of the main constraints in the practical implementation of biofuels at global scale. Therefore, the present investigation is focused to produce low-cost cellulase via sustainable strategies. This work evaluates to achieve enhanced fungal cellulase production using natural and pretreated sugar cane bagasse (SCB) via Rhizopus oryzae NS5 under the solid state fermentation (SSF) while implementing graphene oxide (GO) as a catalyst. A low alkali treatment showed better performance for cellulase production wherein 14 IU/gds FP activity is observed in 96 h using 0.5% alkali treated SCB, significantly higher as compared to 10 IU/gds FP in case of untreated SCB. Further, the effect of GO has been investigated on cellulase production, incubation temperature and pH of the production medium. Under the influence of 1.5% concentration of GO, alkali pretreated SCB produced maximum 25 IU/gds cellulase in 72 h at pH 5.0 and 40 °C.